2016
DOI: 10.1504/ijssoc.2016.074948
|View full text |Cite
|
Sign up to set email alerts
|

Predicting behaviours related to marine litter prevention: an empirical case based on junior high school students in Italy

Abstract: Like many other environmental issues, marine litter represents a growing threat that needs to be tackled appropriately. Young adults can play a crucial role in targeting current and future issues related to marine litter given that they tend to be particularly aware of factors regarding sustainability and the environment in general. The study investigates the willingness of junior high school students to be involved in supporting beach clean-up activities and other awareness programs related to marine litter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 51 publications
(91 reference statements)
3
12
0
Order By: Relevance
“…attitude has limited explanatory power to explain preventive-related behaviour such as marine litter prevention (Gusmerotti et al, 2016) and waste prevention behaviour (Corsini et al, 2018). In addition, the study by Corsini et al (2018) found that waste prevention behaviour is more likely to be explained by injunctive norms, moral norms and perceived behavioural control but not by attitude.…”
Section: Food Waste Prevention Behaviourmentioning
confidence: 98%
“…attitude has limited explanatory power to explain preventive-related behaviour such as marine litter prevention (Gusmerotti et al, 2016) and waste prevention behaviour (Corsini et al, 2018). In addition, the study by Corsini et al (2018) found that waste prevention behaviour is more likely to be explained by injunctive norms, moral norms and perceived behavioural control but not by attitude.…”
Section: Food Waste Prevention Behaviourmentioning
confidence: 98%
“…This result aligns with those of Anderson [ 83 ], who found that, among TPB variables, subjective norms had the strongest positive impact on powerful variable behavioral intentions and PEBs among university students in the United States. Similarly, Gusmerotti et al [ 84 ] found that subjective norms were the strongest predictor of high school students’ PEBs related to marine litter in Italy, while attitude had a limited impact. Halder et al [ 85 ] found that subjective norms had the second-strongest positive impact on high school students’ intentions to use bioenergy.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, De Leeuw et al [ 82 ] found that of the studied variables, attitude had the least power to predict high school students’ intentions to perform pro-environmental behaviors [ 82 ]. Gusmerotti et al [ 84 ] also found that attitude had a limited impact on high school students’ PEBs related to marine litter in Italy. In contrast, Swaim [ 87 ] found that, among TPB constructs, attitude had the strongest influence on college and university students’ intentions to engage in behaviors promoting environmental sustainability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, according to Kaur et al (2020) cities and local authorities (Zorpas et al, 2015a) are challenged by providing these services mainly due to drivers and related pressures on waste management infrastructures which effects the LOS. Moreover, waste strategies must also emphasise (Gusmerotti et al, 2016; Kiessling et al, 2017) on young adults to address the marine litter problem and to identify environmental knowledge and social norms as shaping factors for pro-environmental behaviour.…”
Section: Methodsmentioning
confidence: 99%